John Murtagh's patient education - Murtagh, John 1936- (McGraw-Hill Education Medical, 2012)
Suitable for doctors in practice, general practice nurses, medical students, pharmacists and consumers needing accurate information in an age of internet selfishness, this edition includes 40 new information sheets, bringing the total number of subjects close to 350, and existing sheets and illustrations have been updated with the information.